A 44-DAY OLD MALE INFANT WITH THORACOABDOMINAL ECTOPIA CORDIS OF PENTALOGY CANTRELL’S SYNDROME - Yuliantini, Tri; Gunawijaya, Eka; Putu Yasa, Ketut (Medicina, 2013)
Ectopia cordis is a rare and impressive congenital abnormality, occurring in 5.5 to 7.9 per 1 million live births. The defect is characterized by partial or complete displacement of the heart out of the thoracic cavity. This defect require a staged procedure to achieve a complete repair. We reported a 44-day-old male infant presented with symptoms of tachypnea and mild cyanosis since birth. On physical examination, the child looked lethargic with a weak cry. The midline defect extended from the lower margin of the neck to the umbilicus. The sternum was completely bifid, with an inter-ridge distance of 6 cm, through which the heart was protruded for 4-5 cm and the apex pointed anteriorly. The first and second heart sounds were normal with ejection holosystolic murmur. The diagnosis was ectopia cordis. A two dimensional echocardiography showed complete atrioventricular septal defect, which was known as a group of cyanotic congenital heart defect. The infant was referred subsequently to the neonatal intensive care unit with the ventilator support. Historically, the prognosis of this condition is poor. Our patient died before surgery being performed.